Balance Analysis of the Mobile Anthropomimetic Robot Under Disturbances – ZMP Approach. (22nd April 2013) - Antoska, Vesna; Jovanović, Kosta; Petrović, Vladimir M.; Baščarević, Nenad; Stankovski, Mile
Throughout the history of technological progress, attempts have been made to build a machine that looks and behaves like humans. This paper presents a semi-anthropomimetic robot. The robot structure consists of a human-like upper body mounted on a mobile platform (mobile base, cart). The robot uses the three-wheeled mobile platform with two driving wheels and one passive (caster) wheel. The configuration and model of the upper body are represented as an anthropomimetic, compliant robot with antagonistically coupled drives. Robust control is evaluated in order to ensure stability of the robot position. The aim of this work is not the synthesis of control, but rather the examination of the limits of the adopted robot control strategy and the robot behaviour under disturbances (analysis of tip-over stability). The paper analyses both disturbances from the cart motion and external disturbances due to interaction with the environment (external impulse and long term external force). In order to analyse the balance of the robot and to avoid tipping over, different situations are tested and the appropriate dimensions of the cart are estimated (relying on the ZMP calculation).